Regional Economic Growth and SMEs in Brazil: a Spatial Analysis (Submission for the Refereed Y-session Papers). - Túlio Cravo (European Regional Science Association (ERSA), 2010)
This paper examines the relationship between economic growth and the Small and Medium Enterprise (SME) sector for a panel of 503 Brazilian micro-regions for the period 1980-2004 using panel spatial econometrics. It investigates the importance of the SME sector size measured by the share of the SME employment in total employment, and the level of human capital in the SME sector measured by the average years of schooling in SMEs. The exploratory spatial data analysis show strong evidence accounting for the existence of spatial dependence and indicate the use of spatial econometrics techniques to provide a more comprehensive analysis of the importance of entrepreneurship for regional economic growth. The empirical results indicate that the relative importance of SMEs (size of SME sector) is negatively correlated with economic growth. On the other hand, human capital embodied in SMEs present a positive and significant impact on economic growth. Moreover, the interaction of the relative size of the SME sector across space is positive and statistically significant for growth, suggesting that more SMEs in neighbouring regions incites productive entrepreneurship and new economic possibilities that affect economic performance positively. This is in line with the idea that entrepreneurial activities have a more positive influence on neighbouring regions than on distant regions due to cultural aspects. Besides, the spatial lag of human capital in SMEs is negatively related with growth and indicates that a given region does not benefit from a higher level of human capital in the neighbouring region; SMEs in regions with higher level of human capital only attract more skilled labour from neighbouring regions and do not generate any spillover for those regions. Therefore, a SME policy that subsidizes the creation of SMEs does not generate economic growth directly but through spatial interactions. Additionally, the promotion of human capital in SMEs seems to be important for regional growth, although there is no human capital spillover in the SME sector.
Keywords: O10; L11; R11; C31; 330; Firm size; market structure; economic growth; spatial econometrics